2002
DOI: 10.1063/1.1477942
|View full text |Cite
|
Sign up to set email alerts
|

A class of boron-rich solid-state neutron detectors

Abstract: Real-time solid-state neutron detectors have been fabricated from semiconducting boron-carbon alloys, deposited by plasma-enhanced chemical vapor deposition. Single neutrons were detected and signals induced by gamma rays were determined to be insignificant. The source gas closo-1,2-dicarbadodecaborane ͑ortho-carborane͒ was used to fabricate the boron-carbon alloys with only the natural isotopic abundance of 10 B. Devices made of thicker boron-carbon alloy layers enriched in 10 B could lead to increased detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
98
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 20 publications
2
98
0
Order By: Relevance
“…Recently, Robertson et al [16], have reported the fabrication of a diode from 270 nm boron carbide layer deposited on n-type Si. They exposed the device to a nuclear reactor, acquired pulse-height spectra, and ascribed features in the spectra to the reaction products of the 10 B(n, α) 7 Li reaction.…”
mentioning
confidence: 99%
“…Recently, Robertson et al [16], have reported the fabrication of a diode from 270 nm boron carbide layer deposited on n-type Si. They exposed the device to a nuclear reactor, acquired pulse-height spectra, and ascribed features in the spectra to the reaction products of the 10 B(n, α) 7 Li reaction.…”
mentioning
confidence: 99%
“…The small number of counts, after placing the Cd foil in position may also be the result of unsuccessfully moderated non-thermal neutrons for the PuBe source. The boron carbide heterojunctions diodes were also found to be insensitive to a 60 Co gamma source [1,2].…”
mentioning
confidence: 99%
“…Semiconducting boron carbide represents a new class of semiconducting materials with potential applications in neutron detection and radioactive decay calorimetry [1][2][3][4][5][6][7]. Boron carbide thin fi lm diodes and devices have begun to attract attention as potentially highly effi cient solid state neutron detectors [8][9][10].…”
mentioning
confidence: 99%
See 2 more Smart Citations